Analysis of the Improvement of Maritime Safety through Seafarer Skills Training Cooperation between Poltekpel Surabaya and the Main Shipping Office of Tanjung Perak - Kusumawati, Elly (Green Publisher Indonesia, 2023)
One effort to enhance seafarer skills is by improving knowledge. Increasing knowledge can be achieved through the implementation of training for ship crews. Through training implementation, it is expected to minimize ship accidents caused by human error, thereby improving maritime safety. This research aims to understand the regulations regarding navigation in the Tanjung Perak harbor area and analyze the role of seafarer skills training in enhancing maritime safety. The method used in this research is qualitative. The data used in this study are primary data obtained directly from respondents through questionnaires and secondary data collected from other sources. The research results show that in the event of an accident within the jurisdiction of the Tanjung Perak Port Master, based on the Minister of Transportation's Decree No. 55 of 2006 concerning Procedures for Ship Accident Inspections, if a ship accident occurs, such as sinking, burning, collision, or grounding, the ship's Master or leader who experiences the accident must report it to the Port Master at the nearest or first port visited. The research also indicates that the implementation of seafarer skills training has an impact on maritime safety. Improving maritime safety can be achieved by participating in self-development activities to enhance the quality of ship personnel (seafarers) for better performance.